Tax competition in a Bertrand-Edgeworth model - Günther G. Schulze; Karl-Josef Koch (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1990)
Tax competition of two countries for foreign direct investment is analyzed in a Bertrand-Edgeworth dyopoly model. In the Symmetrie case zero-taxation is the unique equilibrium in pure strategies. If assymmetries are introduced only e-equilibria will exist. However, if the tax rate applies to foreign direct investment as well as to domestic sources (i.e. players have an outside option) there is no equilibrium in pure strategies.
Keywords: 330